EValuation of the thixoformability of AA7004 and AA7075 alloys - Zoqui,Eugenio José (2010)
This study involved a complete evaluation of the thixoformability of AA7004 and AA7075 alloys, from their microstructural characterization to their viscous behavior. The alloys were subjected to globularization heat treatments for 0, 30, 90 and 210 seconds in two conditions of solid fractions, 45 and 60%, and to viscosity assays under the same conditions. Heat treatments promote the globularization of primary phase particles; hence, the best viscosity results were achieved for alloys with low solid fractions heat-treated for 210 seconds. Alloys AA7004 and AA7075 showed an apparent viscosity of 10(4) to 10(5) (Pa.s). The behavior of materials in this range is similar to that of molten glass and they show high formability. However, the AA7075 alloy showed a better performance than the AA7004 due to the smaller size of its primary particles and original grains, their lower growth during reheating, and depending on the condition, their viscosity of 10(4) Pa.s, which is extremely low for thixoforming standards.